Socio-environmental conflicts and the path to greater environmental justice: interpretations by social work educators. - Sepúlveda Hernández, Elia (Social Work Education, 2024)
The article presents the results of a study conducted in northern Chile that sought to determine how social work educators interpreted the socio-environmental conflicts taking place in their territories. Based on these interpretations, we discuss the educational capabilities required to guide learning processes that ultimately result in greater environmental justice. The study was qualitative, comprising interviews and content analysis. Our findings indicate that extractivism, the absence of the state, and the political struggle between extracting and conserving must comprise the backdrop against which we think about pedagogical processes focused on environmental ethics, the eco-territory, and critical thinking regarding our professional role and its complexities.